Ответ(ы) на вопрос:
1-5(2-3х)=6 7-3(х+1)=6 1-5(2-3x)-6=0 7-3(x+1)-6=0 -5-5(2-3x)=0 1-3(x+1)=0 -5+5(3x-2)=0 1-(3x+3)=0 -5+(15x-10)=0 1-3x-3=0 -5+15x-10=0 -2-3x=0 -15+15x=0 -3x-2=0 15x-15=0 -3x=2 15x=15 3x=-2 x=15:15 x=(-2):3 x=1 x=-²₃
1) [latex]1-5(2-3x)=6[/latex] [latex]1-10+15x=6[/latex] [latex]15x-9=6[/latex] [latex]15x=6+9[/latex] [latex]15x=15[/latex] [latex]x=15:15[/latex] [latex]x=1[/latex] ____________________________________________ [latex]1-5\cdot(2-3\cdot1)=6[/latex] (это проверка) [latex]1-5\cdot(2-3)=6[/latex] [latex]1-5\cdot(-1)=6[/latex] [latex]1+5=6[/latex] [latex]6=6[/latex] ============================================ 2) [latex]7-3(x+1)=6[/latex] [latex]7-3x-3=6[/latex] [latex]4-3x=6[/latex] [latex]3x=4-6[/latex] [latex]3x=-2[/latex] [latex]x=-2:3[/latex] [latex]x=-\frac{2}{3}[/latex]
Не нашли ответ?
Похожие вопросы